1986
DOI: 10.1152/ajpregu.1986.251.2.r398
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of zinc metabolism and its regulation in normal humans

Abstract: Zinc metabolism was studied in 32 normal volunteers after oral (n = 25) or intravenous (n = 7) administration of 65Zn. Data were collected from the blood, urine, feces, whole body, and over the liver and thigh regions for 9 mo while the subjects consumed their regular diets (containing 10 mg Zn ion/day) and for an additional 9 mo while the subjects received an exogenous oral supplement of 100 mg Zn ion/day. Data from each subject were fitted by a compartmental model for zinc metabolism that was developed previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 0 publications
8
120
0
1
Order By: Relevance
“…These were: L (1,24); L(12,1); L(24,23). All other rate constants were not affected by dietary Cu level and their values did not differ by more than 4 % from those found by Wastney et al (1986). Compartment masses were also in agreement with those predicted by Foster et al (1979) and Wastney et al (1986).…”
Section: Studiessupporting
confidence: 83%
See 3 more Smart Citations
“…These were: L (1,24); L(12,1); L(24,23). All other rate constants were not affected by dietary Cu level and their values did not differ by more than 4 % from those found by Wastney et al (1986). Compartment masses were also in agreement with those predicted by Foster et al (1979) and Wastney et al (1986).…”
Section: Studiessupporting
confidence: 83%
“…These two assumptions lead to an inherent overestimation of EZP. Miller et al (1994) found this overestimation to be about 24 % when they fitted their data to a compartmental model (Wastney et al 1986). The subsequent paper (Miller et al 1998) found an overestimation of about 28 %.…”
Section: Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal nucleic acid and protein metabolism, as well as cell growth, division, and function, require sufficient availability of zinc (Vallee and Falchuk 1993). The human body contains 2Á3 g zinc, and nearly 90% is found in muscle and bone (Wastney et al 1986). On the cellular level, 30Á40% of zinc is localized in the nucleus, 50% in the cytosol and the remaining part is associated with membranes (Vallee and Falchuk 1993).…”
Section: Discussionmentioning
confidence: 99%